Effect of Oral Contraceptive Pill Pretreatment on Pregnancy Rates in Patients Stimulated with GnRH Antagonists and rFSH for ICSI - Kumar, Dr. Soni Ashish; N, Dr. Reddy Sanjeeva (International Journal of Innovative Research in Medical Science, 2020)
Background: After the recent introduction of GnRH antagonists in ovarian stimulation, OCP has been used for cycle scheduling purposes. Cycle programming has become more difficult with the use of GnRH antagonists, as stimulation initiation is dependent on the occurrence of menstruation. To overcome this limitation in the GnRH antagonist protocol, patients can be offered the use of pretreatment with oral contraceptive pills (OCP). Objective: To evaluate the effect of oral contraceptive pills (OCP) pretreatment on pregnancy rate in GnRH antagonist cycles. Design: Observational cohort study. Setting: Observational study performed at Sri Ramachandra institute of higher education & research Chennai. Patients: Total 115 patients included in the study from January 2019 to December 2019. All patients divided into two groups, oral contraceptives pretreated group (n-64) and oral contraceptives non treated group (n-51). Results: All oral contraceptives pretreated patients required significantly higher dose of gonadotropins (4745±1476 versus 3659±1230;P <0.0005) and significantly longer days of stimulations (12.2±1.2 versus 10.5±0.8;P <0.0005) in comparison to non-oral contraceptives treated group. There were no difference in total oocytes retrieved and fertilization rate. There were no other differences in cycle characteristics between groups. Implantation and pregnancy rates were not affected by OCP pretreatment. Conclusions: OCP pretreatment use for synchronization of follicles and cycle scheduling in GnRH-antagonist protocol, though it may be associated with longer stimulation and higher gonadotropin consumption but similar pregnancy rates.